Market entry strategies internationalization theories, concepts and cases - Glowik, Mario (De Gruyter Oldenbourg, 2020)
This entirely revised and updated third edition of Market Entry Strategies continues to combine the profound explanation of internationalization theories and concepts with real-life firm cases. Reviewing the readers’ valuable feedback from successful previous editions this version targets to improve the readability. New firm cases of Delivery Hero and Tesla contribute to broaden the books’ industry focus. Particular attention is paid on the case studies developed to exercise in light of business practice what is theoretically taught and explained in the textbook. Through its link to digital learning tools such as charts available to the public at YouTube this new edition provides best pre-requisites for distance learning environments
Keywords: EPRG Model; Location Theories; Market Entry Strategies; Product Life-Cycle Theory; Uppsala Model of Internationalization; BUSINESS & ECONOMICS / Management; Markteintrittsstrategie; Technologieunternehmen; Internationalisierung; Asien; Europa